Antecedents and consequences of brand love: The interplay between the self, engagement and attachment consequences - Kuşçu, Aslı. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2016., 2016)
The current study contributes to research and theory in marketing by presenting a holistic framework to analyze the effects of brands' hedonic, functional, and symbolic resources on brand love and its complex mechanisms with brand engagement, loyalty, word-of-mouth and willingness-to-price-premium using a large array of product categories and a large sample of consumers. In terms of consumer– brand relationships we extend theory by identifying two routes for brand love creation based on the type of primary benefit consumers associate with the brand: one goes through a cognitive consumer-brand identity evaluation and integration leading eventually to love; and here the hedonic positioning of the brand plays a role. The second way is when consumers develop feelings towards brands directly through symbolic and functional experiences. Product category differences influence the effects' strengths. As a second contribution, our findings indicate that cognitive brand engagement and brand love are closely linked to each other. We also find a moderate connection between affective engagement and brand love, but not for behavioral engagement. Lastly, we observe that considering the influence of brand love and engagement on word-of- mouth, loyalty, and willingness-to-price-premium, brand love is a stronger predictor for word-of-mouth and loyalty, whereas it is behavioral engagement for willingness-to-price-premium. Our findings enhance both theory on consumer-brand relationships over the delineated holistic framework and provide implications for practitioners to create and maintain strong, committed relationships with their consumers.
Keywords: Brand loyalty.